2014
DOI: 10.29173/istl1617
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Physical Sciences, Engineering and Mathematics Faculty Regarding Author Fees in Open Access Journals.

Abstract: Discussions of the potential of open access publishing frequently must contend with the skepticism of research authors regarding the need to pay author fees (also known as publication fees). With that in mind, the authors undertook a survey of faculty, postdocs, and graduate students in physical science, mathematics, and engineering fields at two research universities (Cornell University and Syracuse University) asking for their experience with and opinion of paying author fees for publication of research in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In their survey of authors who had published in OA journals that charged APCs, Solomon and Björk (2012b) found that, although significant, OA was a less important factor than the fit of the manuscript within the subject area of the journal, scientific quality of the journal and speed of review and publication. Cusker and Rauh (2014) surveyed the physical sciences, engineering and mathematics faculty at two American research universities. The results indicated that most respondents had not decided against publishing in an OA journal due to APCs.…”
Section: Authors' Views and Behaviour Regarding Apcsmentioning
confidence: 99%
“…In their survey of authors who had published in OA journals that charged APCs, Solomon and Björk (2012b) found that, although significant, OA was a less important factor than the fit of the manuscript within the subject area of the journal, scientific quality of the journal and speed of review and publication. Cusker and Rauh (2014) surveyed the physical sciences, engineering and mathematics faculty at two American research universities. The results indicated that most respondents had not decided against publishing in an OA journal due to APCs.…”
Section: Authors' Views and Behaviour Regarding Apcsmentioning
confidence: 99%
“…Nevertheless, certain researchers have expressed reservations regarding open access. On the one hand, studies have indicated that open access journals (OAJs) are frequently perceived as having a lower quality compared to well-established and prestigious subscription journals [32,33]. The overwhelming consensus among researchers is that the quality and prestige of a journal are pivotal factors when selecting a venue for publishing their articles [23,34].…”
Section: Researchers' Awareness Towards Oamentioning
confidence: 99%